The connections between group maturity, software development velocity, and planning effectiveness. Issue 1 (12th September 2017) - Al‐Sabbagh, Khaled Walid; Gren, Lucas
Abstract: Empirical evidence regarding the connection between group development (maturity) and the success of software development teams is lacking. The purpose of this research is to gain a qualitative and quantitative understanding of how velocity and planning effectiveness of software teams connect to a group development model. The Group Development Questionnaire was given to 19 software developers from 4 work groups to assess their group development maturity. The work groups' responses to the survey were checked for correlation with development velocity and planning effectiveness. Semistructured interviews were conducted with 16 individuals from the same 4 work groups to explore issues about their group maturity and to validate the responses of the interviewees in the Group Development Questionnaire. The measurement of the fourth stage of group development had a strong association with the planning effectiveness measurement, which means that a team with less issues in the fourth phase of group development is more effective in adhering to its plans. On the other hand, group development and velocity showed no significant convergent validity. We conclude that the dynamics within software development teams might correlate to their ability to deliver the expected outcome as planned but not to their ability to develop tasks faster. Abstract : The measurement of the fourth stage of group development had a strong association with the planning effectiveness measurement, which means that a team with less issues in the fourth phase of group development is more effective in adhering to its plans. On the other hand, group development and velocity showed no significant convergent validity. We conclude that dynamics within software development teams might correlate to their ability to deliver the expected outcome as planned but not to develop tasks faster.